2012
DOI: 10.1007/s11625-011-0155-z
|View full text |Cite
|
Sign up to set email alerts
|

Governance for sustainability: knowledge integration and multi-actor dimensions in risk management

Abstract: Sustainability has many dimensions, including various aspects of environmental, social and economic sustainability. This paper proposes an analytical framework of risk-related governance for sustainability, based on literature review, focusing on two dimensions-knowledge integration and multi-actor governance. Knowledge integration necessitates wider coverage of predicted and anticipated risks and information on those risks. Multiactor governance necessitates mechanisms that enable cooperation among actors. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 61 publications
0
47
0
3
Order By: Relevance
“…These challenges are not bounded by disciplines but instead require the engagement of a different type of knowledge borne by different stakeholders [107]. This view is supported by other authors [108], who identified two main dimensions in the analytical framework of governance for sustainability: multi-actor governance and knowledge integration.…”
Section: Governancementioning
confidence: 73%
“…These challenges are not bounded by disciplines but instead require the engagement of a different type of knowledge borne by different stakeholders [107]. This view is supported by other authors [108], who identified two main dimensions in the analytical framework of governance for sustainability: multi-actor governance and knowledge integration.…”
Section: Governancementioning
confidence: 73%
“…Governance for SD, in light of a "wicked problem", has to be conceptualised as "steering requirements" that facilitate a continuously emerging policy approach rather than the management/steering/guiding of the implementation of a particular policy [16][17][18][46][47][48][49]. These "steering requirements" are conceptualised in this paper through governance for SD principles that facilitate SD as a "clumsy" solution approach.…”
Section: Governance For Sd Principles As a Clumsy Solution Approach Fmentioning
confidence: 99%
“…With respect to the other policies (policy Nos. 5,12,15,18), it can be seen that generally these policies require larger populations and employment bases to sustain them, in particular policy no. All of the policies identified as common to medium sized settlement change scenarios are applicable in larger settlements, pointing to the finding that medium sized settlements can become more sustainable by emulating larger more sustainable settlements on a pro-rata basis.…”
Section: Appropriate Settlement Sustainability Policymentioning
confidence: 99%
“…Robust evidence is required and linkages between researchers and policy-makers need to be further strengthened [15,16]. There is a recognized need for more empirical studies on policy appraisal [17,18]. Evidence based policy-making has been adopted to facilitate a more rational and systematic process, representing a departure from ideological opinion based policy-making [19,20].…”
Section: Introductionmentioning
confidence: 99%